2011
DOI: 10.1007/s11748-010-0667-y
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular perforation and dissecting subepicardial hematoma after catheter ablation for Wolff-Parkinson-White syndrome

Abstract: Radiofrequency catheter ablation of accessory bypass tracts has become a widely accepted therapy for Wolff-Parkinson-White (WPW) syndrome. The procedure typically has a high success rate with a low incidence of complications. Left ventricular perforation is a rare but serious complication of catheter ablation. Here we describe a patient who developed left ventricular perforation and a dissecting subepicardial hematoma with cardiac tamponade following catheter ablation for WPW syndrome. Immediate hematoma evacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Nagamine et al 8 also described a similar mechanism leading to LV perforation and dissecting subepicardial haematoma, repaired by…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nagamine et al 8 also described a similar mechanism leading to LV perforation and dissecting subepicardial haematoma, repaired by…”
Section: Discussionmentioning
confidence: 95%
“…If direct mechanical perforations by the catheter's tip seem to occur predominantly during the right ventricle ablations, LV myocardial traumas are often related to the “steam pop” phenomenon which is caused by excessive intramyocardial heating with subsequent steam formation and abrupt volume expansion, 6 as described by Tokuda et al 7 in a series of 892 consecutive patients (incidence of perforation 1%; despite routine utilization of irrigated‐tipped catheters specifically designed the steam pop injury was responsible for 60% of the perforations). Nagamine et al 8 also described a similar mechanism leading to LV perforation and dissecting subepicardial haematoma, repaired by transmural incision of the injured myocardium under cardio pulmonary by‐pass (CPB) and use of horizontal mattress sutures buttressed with teflon felt strips. In a similar way Cao et al 9 also presented a case of apical LV perforation, secondary to RFCA which was repaired with teflon buttressed sutures and use of a patch on CPB.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in the "borderline" or "low risk" case more and more electrophysiologists are opting for ablation. While one could argue that there are risks (including perforation, coronary injury and AV block) associated with ablation, these risks are low and manageable compared to the low though still unclear risk of sudden death [25][26][27][28]. With current risk assessment strategies that are far from perfect and with the real risk of sudden death in young athletes truly unknown, a judicious and careful attempt at ablation that blends risk assessment parameters and patient safety seems to be a reasonable approach.…”
Section: Role Of Isoproterenol Testingmentioning
confidence: 99%
“…The recent 2015 AHA/ACC/HRS guideline committee review may not have found the hard evidence to emphasize an increased occurrence of life threatening complications in the “real world” relative to high volume centers but this would not be difficult to believe . Reported life threatening complications (even in the modern era of catheter ablation in experienced centers) include mitral valve injury requiring surgical mitral valve repair, coronary artery injury including total coronary stenosis and aborted death, left main coronary occlusion, left ventricular perforation and death and numerous others. The recent registry data reported a low, albeit not zero, complication rate associated with AP ablation, even in high‐volume experienced centers …”
Section: Introductionmentioning
confidence: 99%